2002
DOI: 10.1128/aac.46.6.2024-2028.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a Cation Efflux Pump Gene Associated with Chlorhexidine Resistance in Klebsiella pneumoniae

Abstract: Expression libraries of a chlorhexidine-resistant Klebsiella pneumoniae strain were constructed and transformed into Escherichia coli XLOLR. Twenty chlorhexidine-resistant transformants were obtained after selection. All clones contained a novel 903-nucleotide locus. Its sequences were compatible with a cation efflux pump, and the locus was thus designated as cepA. Retransformation using cepA-containing plasmids conferred chlorhexidine resistance to both XLOLR and a chlorhexidine-sensitive K. pneumoniae strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 19 publications
4
54
0
Order By: Relevance
“…The same condition was reported for S. enterica (17). Garaizar Typhimurium LT2 by microarray analysis and reported that a region including 13 genes responsible for the anaerobic assimilation of allantoin as a nitrogen source was absent in all S. enterica serovar [4,5,12:i:Ϫ] strains but was present in serovar Typhimurium LT2 strains. However, the physiological implication of the deletion in S. enterica remains unclear.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The same condition was reported for S. enterica (17). Garaizar Typhimurium LT2 by microarray analysis and reported that a region including 13 genes responsible for the anaerobic assimilation of allantoin as a nitrogen source was absent in all S. enterica serovar [4,5,12:i:Ϫ] strains but was present in serovar Typhimurium LT2 strains. However, the physiological implication of the deletion in S. enterica remains unclear.…”
Section: Discussionmentioning
confidence: 61%
“…The phagemid library was obtained by using a Gigapack III Gold packaging kit (Stratagene) as previously described (12). A total of 5,760 clones were amplified by PCR with primers in vector ( Table 2), and 3,146 of these clones were randomly selected for the microarray.…”
mentioning
confidence: 99%
“…A few AcrAB multidrug efflux systems have been characterized in Klebsiella spp. (7,20,23,28), but the sequencing data of K. pneumoniae strain MGH78578 show that many others potentially are present, as in closely related E. coli species (3). In this study, we characterized a gene cluster in K. pneumoniae LM21 that exhibits strong homologies with the EefABC RND efflux system-encoding operon, initially described in E. aerogenes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence is still ambiguous, assertions have been made that other antimicrobials might similarly select for resistance and that biocides in general could affect susceptibilities to chemically unrelated compounds (11,24,25,40). With respect to CHX, use of this biocide has been associated with decreased susceptibility in hospital surveys (1,21), while a recent report has associated a cation efflux pump with decreased CHX susceptibility in Klebsiella pneumoniae (8). Daily dental hygiene applications of CHX in human volunteers over 2 years, however, resulted in only a slight change in distribution toward those organisms which were less sensitive to CHX (38).…”
mentioning
confidence: 99%